Lipoprotein X in a patient with cholestasis and hypertriglyceridaemia. (March 2013) - Stepien, Karolina M; Divyateja, Hrushikesh; Ahmed, Farhan; Prinsloo, Peter; Gupta, Pankaj
Hypertriglyceridaemia is an established cause of acute pancreatitis and responds to insulin therapy in addition to lipid lowering medication. We report a case of severe hypertriglycaeridemia of 149 mmol/L in a 36–year–old man with type 2 diabetes who presented to the surgical ward with abdominal pain due to pancreatitis and developed acute cholestasis, jaundice and eruptive xanthomata. His triglycerides improved to 3.8 mmol/L with sliding scale insulin within two weeks of in-hospital stay. However, his total cholesterol remained raised at 23.7 mmol/L. The lipoprotein electrophoresis confirmed the presence of lipoprotein X associated with bile obstruction, which contributed to an increase in total cholesterol. The total cholesterol normalized on improvement of his cholestasis.